Does she think it matters who makes more? Perceived differences in types of relationship arguments among female breadwinners and non-breadwinners - Melanie Mendiola; Julia Mull; Kristy L Archuleta; Bradley Klontz; Farnoosh Torabi (Journal of Financial Therapy, 2017)
This mixed methods study used a sequential exploratory design and Becker’s (1973) Theory of Marriage to explore how female breadwinners and non-breadwinners perceive types of relationship arguments. Respondents completed an online survey targeted to women about money and relationships. Qualitative analyses using a multiple case study approach explored the contents of arguments among three groups: women who earn more than their partner/spouse, women who earn less, and women who earn the same. Quantitative analyses employed independent t-tests to identify differences between female breadwinners and non-breadwinners for variables related to the identified themes from the qualitative analyses. Findings from this mixed methods study suggest that female breadwinners tend to perceive their partners as not meeting their expectations, are more likely to use blame language, and are less likely to use “togetherness” language when describing relationship arguments. Implications for future research and practice are provided.
Keywords: income disparity; marital arguments; money arguments; women; couples; female breadwinner; qualitative; mixed methods